Acute pulmonary edema and emphysema in cattle in Southern Brazil: Spontaneous disease and experimental reproduction Edema e enfisema pulmonar agudo em bovinos no Sul do Brasil: Doença espontânea e reprodução experimental - Wicpolt N.S.* (2014)
The paper reports the epidemiological data, clinical signs and lesions of four outbreaks of acute pulmonary edema and emphysema in cattle (ABPE) which occurred in the states of Parana and Santa Catarina, as well as its experimental reproduction. The spontaneous disease occurred after the cattle was transferred from a mature and dry pasture to another luxurious sprouting one. All affected animals were adult dairy cows of Holstein and Brown Swiss breed. The main clinical signs were dyspnea of laborious abdominal breathing with extended neck and open mouth. The sick animals also presented subcutaneous emphysema, decreased milk production, slow recovery or death. Postmortem findings were restricted to a dark red not collapsed lung, which was shiny and hyper sizzling more than usual and with marked interlobular emphysema. Histological lesions in the lung consisted of alveolar and interlobular emphysema, areas with congestion and edema, hyaline degeneration of the alveolus wall and moderate diffuse infiltration of macrophages and eosinophils. The experimental reproduction of the disease was performed in a cow by orally administration of 0.7mg/kg/LW of L--Tryptophan single dose. The animal died on the seventh day of the experiment. The clinical signs and lesions were similar to those observed in the naturally occurring disease.